Organic multicolor super-heterostructure constructed based on radial assembly mechanism, preparation method and application in anti-counterfeit label - GAO ZHENHUA; MENG XIANGENG; WANG ZIFEI; XU YUYU; YANG SHUO; WANG XUE (2023)
The invention provides an organic multicolor super-heterostructure constructed based on a radial assembly mechanism, a preparation method and application in an anti-counterfeit label. The organic multicolor super heterostructure is a single-module heterostructure or a multi-module integrated super heterostructure; the single-module heterostructure is formed by taking tri (octahydroxyquinoline) aluminum (Alq3) as a subject and Nile red (NR) as a guest molecule through pi-pi interaction; the multi-module integrated super-heterostructure is formed by self-assembling a plurality of single-module heterostructures in the radial direction. The single-module organic multi-color heterojunction structure material is prepared through a simple and low-cost method, and then the multi-module integrated super-heterostructure material is constructed through directional assembly. The single-module heterostructure prepared by the invention is red and green crystals with different dyeing intervals, and can form a spatially reso